The Comparison of LISA and INSURE techniques in term of neonatal morbidities and mortality among premature infants.: The Comparison of LISA and INSURE techniques. - Silahli, Musa; Tekin, Mehmet (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: Respiratory distress syndrome (RDS) is the most common cause of respiratory failure among premature infants. The most important choice for the treatment of RDS is still exogenous surfactant replacement therapy and respiratory support. Today, there are some different surfactant applying techniques. In this study, we aimed to evaluate the effects of the surfactant administration techniques in premature infants less than 33 weeks of gestational age. Methods: The medical data were collected retrospectively from the medical records of Baskent University, Konya Training and Research Hospital between 2010 and 2016. The patient divided into two subgroups as Less Invasive Surfactant Administration (LISA) group (n: 35) and Intubation- Surfactant administration and rapid Extubation (INSURE) group (n: 30). Two surfactant administration techniques were evaluated on the neonatal morbidities and mortality among premature infants. Results: There were no significant differences in maternal and neonatal characteristics between the two groups. Duration on the nasal continues positive airway pressure (nCPAP) is significantly higher in the LISA group as compared with the INSURE group (p<0.001). And also between two groups, there were no significant differences in term of neonatal mortality and morbidities. Conclusion: The technique of the surfactant administration has no effect on the postnatal morbidities. LISA method is safe and effective as much as INSURE method, which is still a good alternative in centers with lack of experience about LISA. We need to perform studies that have larger sample size and prospective randomized controlled trials.